Prophylaxis of asymmetric carriage of schoolboys of middle age by facilities of physical rehabilitation. - Gulbani R.Sh; Zaed Yu.V; Hagner-Derengowska M. (Kharkov National Pedagogical University, 2011)
The questions of violation of carriage are considered in a frontal plane for schoolboys of middle age. In research took part 20 schoolboys (girls and boys) of 12-14 years old. The estimation of the state of carriage is executed. Violations of carriage are exposed with predominance of right-side asymmetry of trunk. The complexes of facilities of physical rehabilitation, the basic component of which are correctings exercises, are offered. Positive influence of complexes, directed on the prophylaxis of asymmetric carriage of schoolboys is certain.